Penerapan Model Problem Based Learning untuk Meningkatkan Pemahaman Konsep IPA Siswa Kelas V SDN Kedai Runding - Faizin Faizin; Patri Janson Silaban; Lasma Silaban (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research was motivated by students' lack of understanding of concepts in science learning taught in grade V SDN Kedai Runding, South Kluet District, South Aceh. The purpose of this study is to provide an overview of students' understanding of improving concepts in science through the Problem Based Learning Model. The difficulty of students in understanding concepts is indicated by the inability to understand concepts, give examples, explain and conclude the subject matter. The research method used is the method proposed by Kemmis and McTaggart, namely Classroom Action Research. The study was conducted in two cycles with 9 students consisting of 3 male students and 6 female students. The average evaluation test score of students in understanding concepts in cycle I is 60% and increases in cycle II to 88%.Based on the results of the study, it can be concluded that the application of the Problem Based Learning model is effective in increasing students' understanding of the concepts in science taught to grade V students of SDN Kedai Runding.